The availability and distribution of health services and resources across different regions in Afghanistan - Hegazy, Nelly; El Deeb, Sherif; Salem, Marwa Rashad; Shaguy, Jerome A.; Mohammed, Ramesh Nassery; Khawari, Abdullah; Tanoli, Jamshed; Abouzeid, Alaa (Frontiers in Public Health, 2025)
Background Ensuring equitable access to healthcare services is fundamental to a robust healthcare system, especially during humanitarian crises. This study analyzes the availability and distribution of health resources across Afghanistan, aiming to provide a data-driven understanding of healthcare resource access and identify potential disparities, a critical aspect of effective humanitarian response planning. Methods: Principal investigators collated related data and literature from databases and data warehouses in a systematic approach using search strings and collection tools to query databases and available data warehouses to assess the availability and distribution of health services and resources across different regions in Afghanistan, with the principal database queried being the Afghanistan Health Resources Availability database (HeRAMS), an electronic and web-based system conceived by the World Health Organization. An Excel version was sourced. Results: The sub-health center represents 31.1% of the health facilities, followed by the basic health center (22.5%) and the mobile health team (17.1%). More than 85% of these facilities are fully operational, with the highest percentage observed in the Southern and Northeastern regions at 96.8%, followed closely by the central highland and Southeastern regions. Outpatient services for primary care are notably prevalent in the Northeastern, Southeastern, Southern, Eastern, and Northern region, conversely, the Capital and Central Highland regions demonstrate the lowest provision of primary care services. Antenatal care services are accessible at a level exceeding 70% in nearly all regions, with the highest accessibility in the Northeastern region at 91.3 %, the prevalence of non-communicable illness clinics was observed to be below 50%, with the highest availability in the Southern region at 49.4%, followed by the Southeastern region. In terms of sanitation facilities, availability surpasses 70% across Afghanistan, with the highest observed in the Northeastern region at 89.2%. Conclusion The study highlights significant disparities in healthcare access across various regions, with notable challenges in the availability of critical services. Furthermore, the study underscores the significant impact of financial constraints and equipment shortages on the functionality of healthcare facilities, particularly in the Northeastern and Western regions. This analysis emphasises the need for targeted resource